Supervised and unsupervised algorithms for bioinformatics and data science - Sohail, Ayesha; Arif, Fatima (Progress in biophysics and molecular biology, 2020)
Bioinformatics refers to an ever evolving huge field of research based on millions of algorithms, designated to several data banks. Such algorithms are either supervised or unsupervised. In this article, a detailed overview of the supervised and unsupervised techniques is presented with the aid of examples. The aim of this article is to provide the readers with the basic understanding of the state of the art models, which are key ingredients of explainable machine learning in the field of bioinformatics.